Drinking and driving and perceptions of arrest risk among California drivers: Relationships with DUI arrests in their city of residence. (18th August 2017) - MacLeod, Kara E.; Karriker-Jaffe, Katherine J.; Satariano, William A.; Kelley-Baker, Tara; Lacey, John H.; Ragland, David R.
ABSTRACT: Objective : Addressing drinking and driving remains a challenge in the United States. The present study aims to provide feedback on driving under the influence (DUI) in California by assessing whether drinking and driving behavior is associated with the DUI arrest rates in the city in which the driver lives; whether this is due to perceptions that one can get arrested for this behavior; and whether this differed by those drivers who would be most affected by deterrence efforts (those most likely to drink outside the home). Methods : This study consisted of a 2012 roadside survey of 1, 147 weekend nighttime drivers in California. City DUI arrest rates for 2009–2011 were used as an indicator of local enforcement efforts. Population average logistic modeling was conducted modeling the odds of perceived high arrest likelihood for DUI and drinking and driving behavior within the past year. Results : As the DUI arrest rates for the city in which the driver lives increased, perceived high risk of DUI arrest increased. There was no significant relationship between either city DUI arrest rates or perceived high risk of DUI arrest with self-reported drinking and driving behavior in the full sample. Among a much smaller sample of those most likely to drink outside the home, self-reported drinking and driving behavior was negatively associated with DUI arrests rates in their city of residence but this was not mediated by perceptions. Conclusion : The results of the present study suggest that perceptions are correlated with one aspect of DUI efforts in one's community. Those who were more likely to drink outside the home could be behaviorally influenced by these efforts.